If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+x/3=x/3+30
We move all terms to the left:
x+x/3-(x/3+30)=0
We get rid of parentheses
x+x/3-x/3-30=0
We multiply all the terms by the denominator
x*3+x-x-30*3=0
We add all the numbers together, and all the variables
x*3-90=0
Wy multiply elements
3x-90=0
We move all terms containing x to the left, all other terms to the right
3x=90
x=90/3
x=30
| 4y-3=y+2 | | ?x6=42 | | 1-x/2=2x+2/3 | | 2.5-2x2=6x | | 4(2x-3)+5(2-x)=6(1-x)=5x | | -22-4z=+10 | | 4x+16+x=64 | | 18x3−8x=0 | | 7=56/m | | 3xx/2=60 | | 9x/11-6=5x/9+4 | | (7x-6)(-8x+1)=0 | | 3x-40=x/2+20 | | 7x+20=5x-9 | | 0=1.5x^2+4x | | Y=7/6x+6 | | 6x-1-(3x-3)=3 | | 2700=6800x | | 8x^2=500 | | 7x+31=10 | | 40÷3q=15 | | 3(x+5)/4+-7(x+3)/10=4 | | 3x/8-3=-5 | | 3*x+x/5-5=1/5+5*x | | 5/8t+14=-1 | | 4q+20=16 | | 12(t+4)-8=88 | | 1/5x+1/3=-1 | | 8c-6=15 | | 2x-8=130 | | x-5/3+4x-9/12=5x-32/9-x+9/21 | | 2(3x+5)=x^2 |